2024
DOI: 10.1039/d4ta00655k
|View full text |Cite
|
Sign up to set email alerts
|

Constructing oxygen vacancies by doping Mo into spinel Co3O4 to trigger a fast oxide path mechanism for acidic oxygen evolution reaction

Lang Sun,
Min Feng,
Yang Peng
et al.

Abstract: The development of non-precious metal electrocatalysts for the acidic oxygen evolution reaction (OER) that are highly durable, cost-effective, and efficient is crucial to advancing the use of proton exchange membrane...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…This enhancement is evidenced by the direct reaction intermediates, i.e., −O–O–, *–O–O, and *OH. Concurrently, the OPM is superior to the AEM because of the reduced increase in free energy and performs better than AEM on Ru/MnO 2 during OER. , …”
Section: Oer Mechanismsmentioning
confidence: 99%
“…This enhancement is evidenced by the direct reaction intermediates, i.e., −O–O–, *–O–O, and *OH. Concurrently, the OPM is superior to the AEM because of the reduced increase in free energy and performs better than AEM on Ru/MnO 2 during OER. , …”
Section: Oer Mechanismsmentioning
confidence: 99%
“…21–23 For example, Xin Yue et al demonstrated that the addition of a few Mo heteroatoms (∼0.5 wt%) to Co 3 O 4 can enhance its activity and stability in the acidic OER. 24 This enhancement can be ascribed to the activation of lattice oxygen by the doping of Mo, leading to a well-defined etching process and oxygen vacancy generation. The obtained oxygen vacancies promote a rapid oxygen evolution reaction (OER) pathway, while the variable valence state of Mo contributes to its stability.…”
Section: Introductionmentioning
confidence: 99%
“…1–5 Developing efficient and low-cost oxygen evolution reaction (OER) catalysts is a major challenge due to the four-electron coupled process and higher energy barriers. 6 Elaborately designed electrocatalysts have been proved to reduce the overpotential and sluggish kinetics at the anode effectively. Transition metal oxide-based catalysts are known as the most active due to their intrinsic electronic structures and binding strength of oxygenated intermediates.…”
Section: Introductionmentioning
confidence: 99%